2022
DOI: 10.3389/fneur.2022.964354
|View full text |Cite
|
Sign up to set email alerts
|

Frictional force analysis of stent retriever devices using a realistic vascular model: Pilot study

Abstract: ObjectiveTo date, no vascular model to analyze frictional forces between stent retriever devices and vessel walls has been designed to be similar to the real human vasculature. We developed a novel in vitro intracranial cerebrovascular model and analyzed frictional forces of three stent retriever devices.MethodsA vascular mold was created based on digital subtraction angiography of a patient's cerebral vessels. The vascular model was constructed using polydimethylsiloxane (PDMS, Dow Corning, Inc.) as a silicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Experiments using more complex vascular models made of silicone rubber [29,[35][36][37][38][39], acrylic [40], poly(vinyl alcohol) hydrogel [25][26][27][30][31][32][33], and elastomer-hydrogel skin multilayers [9,28] that mimic living tissue have also been conducted. 3D printers are widely used to prepare biomodels and can easily fabricate mold copies of the vascular tree, which is subsequently embedded in a liquid resin that solidifies into a solid biomodel.…”
Section: Complex Shapesmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments using more complex vascular models made of silicone rubber [29,[35][36][37][38][39], acrylic [40], poly(vinyl alcohol) hydrogel [25][26][27][30][31][32][33], and elastomer-hydrogel skin multilayers [9,28] that mimic living tissue have also been conducted. 3D printers are widely used to prepare biomodels and can easily fabricate mold copies of the vascular tree, which is subsequently embedded in a liquid resin that solidifies into a solid biomodel.…”
Section: Complex Shapesmentioning
confidence: 99%
“…• It has been reported that continuous insertion at a constant speed into silicone that simulates an aneurysm requires half or less of the maximum force required for intermittent insertion by a doctor, presumably because static friction is exerted when the insertion is paused [35]. • A pulsatile blood pump has been used to generate a pulsating flow with approximately physiological conditions [39]. Khoshbakht et al [98] showed that fluid flow can greatly change the tip contact force when the catheter is close to the left inferior pulmonary vein.…”
Section: Other Parametersmentioning
confidence: 99%
See 2 more Smart Citations